Biomimetic studies on Dosidicus gigas Histidine-rich beak proteins - Cai, Hao (2018)
Over 4 billion years of evolution on earth, Nature has presented countless examples of adaptions towards contextual restraints, which have inspired humankind facing practical engineering problems throughout the entire history of civilization. One intriguing example is Dosidicus gigas (D. gigas) or Humboldt squid, a predatory species of squids often found in the Eastern Pacific Oceans. Ranking among the most formidable hunters in Ocean ecosystems, D. gigas relies largely upon its hunting biotools, one of which being D. gigas beak, an intriguing biological model structure for biomimetic studies. As sharp and tenacious as it is, D. gigas beak is non-mineralized and highly proteinaceous, demonstrating a 200-fold stiffness gradient evolving from soft buccal tissues to the rigid tip. Its constituting proteins, namely D. gigas beak proteins (DgBPs), are believed to play central roles in the formation and sclerotization of the beak material. Among the various members of DgBPs revealed by recent sequencing work, the DgHBP (D. gigas histidine-rich beak protein) family has attracted most interest due to its unique molecular composition and architecture. This thesis therefore focuses on biomimetic studies of DgHBPs, employing a bottom-up approach to gain insights into theirfunctions in vivo. Three parts are included in the thesis. The first part describes the establishment of an optimized production and purification system for DgHBPs. Recombinant expression using E. coli cells carrying engineered gene vectors, followed by purification steps that were developed based on primary solubility studies on DgHBPs, enabled sufficient proteins of high purity to be prepared for subsequently studies. Basic structural characterization of DgHBPs in lyophilized phase and aqueous solution phase are also presented in this part, indicating an important phase-transition feature, which was further explored in the second part. The second part of this thesis highlights the biophysical properties of DgHBPs, in particular their coacervation behavior, which is a liquid-liquid phase separation of a macromolecular solution process under specific conditions, also found in other biological systems such as tropoelastin. Thorough investigation into different aspects (morphology, kinetics, affecting parameters, mechanical properties, thermodynamics, etc.) of the coacervation behavior helped clarifying the roles of DgHBPs during beak formation, and also pointed out the need to study their sequence-coacervation ability relationship. The third part of this thesis examines the sequence-coacervation ability relationship by constructing and studying DgHBPs-based peptides and variants. Different parts from the full sequences of DgHBPs were isolated and tested for their ability to form coacervates, and previous hypotheses about which sequence domains has led to this ability was verified. This thesis highlights important implications of DgHBPs’ phase behavior (coacervation) on D. gigas beak bio-processing. By conducting in vitro studies of DgHBPs, their coacervation ability was examined comprehensively, from the role of the peptide domain aspects to structural and mechanical aspects. A deeper understanding about D. gigas beak formation was obtained, providing inspirations for the design and manufacturing of biomimetic composite materials with tailored mechanical properties, which have relevant potential in medical and engineering applications.